2008
DOI: 10.1016/j.nurt.2007.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Deep Brain Stimulation in Movement Disorders as Revealed by Changes in Stimulus Frequency

Abstract: Summary: Deep brain stimulation (DBS) is an established treatment for symptoms in movement disorders and is under investigation for symptom management in persons with psychiatric disorders and epilepsy. Nevertheless, there remains disagreement regarding the physiological mechanisms responsible for the actions of DBS, and this lack of understanding impedes both the design of DBS systems for treating novel diseases and the effective tuning of current DBS systems. Currently available data indicate that effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 87 publications
(141 reference statements)
6
87
0
Order By: Relevance
“…Alternatively, the model indicated that there was increased synchronization of postsynaptic TC activity at 10 Hz, and this may have contributed to the additional phases and increase in magnitude and/or duration of existing ECAP phases. Clinical symptoms are suppressed only at high DBS frequencies and low frequencies are ineffective or may lead to exacerbation (Birdno and Grill 2008), and the extent of postsynaptic synchronization may contribute to this frequency dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the model indicated that there was increased synchronization of postsynaptic TC activity at 10 Hz, and this may have contributed to the additional phases and increase in magnitude and/or duration of existing ECAP phases. Clinical symptoms are suppressed only at high DBS frequencies and low frequencies are ineffective or may lead to exacerbation (Birdno and Grill 2008), and the extent of postsynaptic synchronization may contribute to this frequency dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The signal energy takes into account changes in either the magnitude or the duration of ECAP phases and may be a more robust measure of neural activation than the ECAP magnitude alone. Similarly, the energy of secondary ECAP phases may enable identification of the critical DBS frequency above which pathological firing patterns are masked and symptoms are suppressed (Birdno and Grill 2008;Kuncel et al 2007). The ECAP could also be used to distinguish between activation of presynaptic inputs or postsynaptic cells that are associated with clinical benefit or side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some models of STN DBS propose that high-frequency stimulation directly inhibits an overactive STN in PD, releasing the basal-ganglia motor circuitry from inhibition [9, 10], suggesting an optimal locus of stimulation within the STN. By contrast, other models propose that high-frequency stimulation of fibers of passage in the STN region replaces pathologic signal information flow in the basal ganglia, without direct STN inhibition [11-14]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite all the importance placed on mechanisms, the mechanisms by which DBS affects the signs of MDs are still unknown despite decades of research using animals [239][240][241]. This is an important element in our analysis of animal models and DBS as one of the reasons animal models in general have been heralded as important, indeed vital, is for the search for mechanisms.…”
Section: Epistemology and Mechanismsmentioning
confidence: 99%